A BARRIER-FREE ENVIRONMENT FOR THE DEVELOPMENT OF ACCESSIBLE TOURISM: DOMESTIC AND FOREIGN EXPERIENCE - N. Ofitserova; O. Solntseva; J. Tsunaeva (Вестник университета)
Creating an accessible environment in accommodation varieties contributes to the development of accessible tourism. The article presents the principles of universal design reflected in the legal documents. The analysis revealed a positive experience of services for guests with reduced mobility. The review of foreign and domestic objects lead to the conclusion that an integrated approach should be adopted, involving the creation of an appropriate hotel infrastructure, as well as urban, transport, etc. Organization of services for guests with disabilities is a social problem actual both in Russia and in other countries whose positive experience should be replicated.